Recursos didácticos en el área de cultura estética énfasis en expresión corporal y su incidencia en la profesionalización de la carrera de educación básica Universidad Técnica de Cotopaxi, extensión La Maná año 2014 - Oña Chicaiza, Myriam Patricia (2015)
The esthetic culture includes important activities in the education of the human being, the same one who allows the acquisition of knowledge, feelings and skill; it is necessary to understand that its beginnings it happens in the infancy, being the family the first one in intervening in the formation of the same ones; nevertheless one has determined that in the students of the school “Dr. Néstor Mogollón López” a deficit exists as for promoting these cultural values, either by factors such as lack of knowledge, lack of efforts by the authorities, lack of interest in this art, among others; is alarming since it affects skills mainly in the body expression which leads to the integral development of the student.